2021
DOI: 10.1177/0269881120965937
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of N-methyl-D-aspartate receptor modulator augmentation in schizophrenia: A meta-analysis of randomised, placebo-controlled trials

Abstract: Background: Dysfunction of the N-methyl- D-aspartate glutamate receptor is involved in the putative pathology of schizophrenia. There is growing interest in the potential of N-methyl- D-aspartate receptor modulators to improve the symptoms of schizophrenia, but the evidence for the use of glutamatergic agents for augmenting schizophrenia remains inconclusive. Aims: We conducted a meta-analysis to test the efficacy and safety of N-methyl- D-aspartate receptor modulator supplements in patients with schizophrenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 86 publications
0
20
0
Order By: Relevance
“…Overall, recent meta-analyses [11] support significant, moderate to large effect size improvements in negative symptoms compared to placebo for pooled NMDA receptor modulators adjunctive to antipsychotics group (SMD = −0.43). Individual compounds with efficacy include glycine (SMD = −0.4), D-serine (SMD = −0.56), and sarcosine (SMD = −0.74).…”
Section: Glutamatergic-based Treatmentsmentioning
confidence: 96%
“…Overall, recent meta-analyses [11] support significant, moderate to large effect size improvements in negative symptoms compared to placebo for pooled NMDA receptor modulators adjunctive to antipsychotics group (SMD = −0.43). Individual compounds with efficacy include glycine (SMD = −0.4), D-serine (SMD = −0.56), and sarcosine (SMD = −0.74).…”
Section: Glutamatergic-based Treatmentsmentioning
confidence: 96%
“…A high dose study in a clinically high risk (CHR) for schizophrenia group (47) also showed significant improvement in prodromal negative symptoms (d = 0.68). Meta-analysis including high dose studies demonstrate moderate to large effect sizes for negative symptoms (3,48), improving on meta-analysis that only include low dose studies (46). D-serine as an adjunct to cognitive remediation has been also been proposed (39,76,77).…”
Section: Use Of D-serine In Treatment Studies: Efficacy and Dose-dependent Effectsmentioning
confidence: 99%
“…D- Serine was originally reported to be beneficial in schizophrenia based upon studies conducted in Taiwan ( 52 ) and Israel ( 54 ). A recent meta-analysis of NMDAR modulators in schizophrenia ( 3 ) has found specific improvement for D -serine adjunctive to antipsychotics for negative symptoms measured by both the Scale for the Assessment of Negative Symptoms (SANS) ( 68 ), with a standardized mean difference (SMD) = −0.56 and the Positive and Negative Symptom Scale (PANSS) negative symptom subscale ( 69 ), with a SMD of −0.49. The meta-analysis for D -serine for total PANSS symptoms was not significant (SMD = −0.3).…”
Section: Use Of D- Serine In Treatment Studies: Efficacy and Dose-dependent Effectsmentioning
confidence: 99%
See 2 more Smart Citations